Two Studies Investigating Associations Between Sexual Assault Victimization History and Bystander Appraisals of Risk - Bridges, Ana J. (Violence against women, 2021)
Across two studies, we examined sexual assault history and bystander appraisals of risk and the moderating roles of danger cue salience (Study 1) and alcohol intoxication (Study 2) in women. Participants (Study 1 = 148, Study 2 = 64) read vignettes ending with cues of nonconsensual sexual activity and an opportunity to intervene. Participants also completed self-report measures of vignette appraisals and history of sexual assault victimization. Across both studies, sexual assault victimization was unassociated with bystander risk appraisals. Alcohol intoxication and subtlety of nonconsent cues did not interact with sexual assault victimization history to influence appraisals of dangerousness.